Enzyme specificity and catalysis - Feigenson, Gerald W. (Henry Stewart Talks, 2020)
Enzyme Commission, Categories of enzymes, Enzyme specificity, Reaction rate, Gibbs function, The Boltzmann distribution, Catalysts role, Catalysts mechanisms
Reviewed at 2022/11/27